XPS study of graphene oxide reduction induced by (100) and (111)-oriented Si substrates. (15th January 2018) - Priante, F; Salim, M; Ottaviano, L; Perrozzi, F
Abstract: The reduction of graphene oxide (GO) has been extensively studied in literature in order to let GO partially recover the properties of graphene. Most of the techniques proposed to reduce GO are based on high temperature annealing or chemical reduction. A new procedure, based on the direct reduction of GO by etched Si substrate, was recently proposed in literature. In the present work, we accurately investigated the Si–GO interaction with x-ray photoelectron spectroscopy. In order to avoid external substrate oxidation factors we used EtOH as the GO solvent instead of water, and thermal annealing was carried out in UHV. We investigated the effect of Si(100), Si(111) and Au substrates on GO, to probe the role played by both the substrate composition and substrate orientation during the reduction process. A similar degree of GO reduction was observed for all samples but only after thermal annealing, ruling out the direct reduction effect of the substrate.